The role of emotions in value creation for families in pediatric health care - Gerritsen, Niina (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
The purpose of this study was to analyze emotions related to a child’s critical illness from the perspective of the family and discuss the link those emotions might form with value creation. High quality service is of paramount importance in hospital care, especially when a child is diagnosed with critical illness. Through the analysis of patient family emotions and their triggers, the study was aiming to deepen the understanding of value creation for customer. Therefore, the research sought to find answers to the following three sub-questions: 1. What are the emotions experienced? 2. What triggers them? 3. How are the emotions linked to amelioration or aggravation of value for patient and family? The theoretical background of this research is built on two core concepts: emotions and value creation. As both concepts are wide and multifaceted, the research concentrates on viewing emotions from the applicable cognitive angle, identifying and categorizing emotions in a general level. Value creation is studied from the service perspective, discussing the possible relations between emotions and value creation. Moreover, the suitability of views regarding customer value co-creation to health care encounters is analyzed. Qualitative approach was selected as the most appropriate methodology for conducting the empirical research. The empirical data was collected from public blogs, for which a total of 18 blogs were reviewed. Five blogs were selected for the analysis, which had the intent of identifying the emotions experienced by patient families and deepening the knowledge of their role in value creation during health care service encounters. The empirical study of this research discovered a wide range of positive and negative emotions, which denotes that a severe life situation does not prevent the feeling of positive emotions. Furthermore, by combining the empirical findings to the theoretical background, this study concludes that recognizing and treating the patient family as a partner and value creator is essential. The high quality technical aspect of care is vital, but it is not the sole attribute for service quality, as the interpersonal communication plays a large role in the customer’s overall assessment of the health care performance. The patients and their families largely evaluate the service encounter based on their perceptions, thus emotions play a significant role. Depending on the service experience, value maybe created or destructed. Hence, this study posits emotion at the core of the service encounter, indicating towards the importance of active assessment of customer perceptions and the recognition of the emotional states